Cyprus : Fifth, Sixth, and Seventh Reviews Under the Extended Arrangement Under the Extended Fund Facility; Request for Waiver of Nonobservance of a Performance Criterion; and Rephasing of Access. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Cyprus's Fifth, Sixth, and Seventh Reviews Under the Extended Arrangement Under the Extended Fund Facility, Request for Waiver of Nonobservance of a Performance Criterion (PC), and Rephasing of Access. Economic developments have been encouraging. The recession in 2014 was milder than expected, and GDP growth was positive in the first quarter of 2015 for the first time in almost four years. Program performance has been generally strong. Compliance with quantitative conditionality has been good, and the authorities have advanced structural reforms. Further efforts to strengthen banking supervision and restructure banks are needed. The ongoing structural reform program is also crucial for public finances and growth.